Malignant Triton Tumor without Von Recklinghausen’s Neurofibromatosis in a 16 year-old Indonesian Girl: A Case Report - Neni Anggraini; Nurjati Chairani Siregar (Majalah Oftalmologi Indonesia, 2017)
Background: To diagnose malignant peripheral nerve sheath tumor with rhabdomyoblastic differentiation in malignant triton tumor which has a rare incidence. Case Illustration: We reported a case in a 16 year-old girl who presented with progressively painless proptosis of the left eye and decreased visual acuity. There was no evidence of Recklinghausen’s disease. She underwent surgery and radiotherapy. The histopatologic findings showed malignant peripheral nerve sheath tumor (MPNST). Four years later, she suffered recurrence proptosis and decreased visual acuity. Histomorphology supported by immunostaining with S-100 protein confirmed the diagnosis of malignant triton tumor. She underwent chemotherapy and enucleation. Conclusion: This case highlights the prudent use of immunohistochemistry that is essential in making an early detection and a correct diagnosis.